A Comprehensive Review of Computational Methods for Automatic Prediction of Schizophrenia With Insight Into Indigenous Populations - Ratana, Randall; Sharifzadeh, Hamid; Krishnan, Jamuna; Pang, Shaoning (Frontiers in Psychiatry, 2019)
Psychiatrists rely on language and speech behavior as one of the main clues in psychiatric diagnosis. Descriptive psychopathology and phenomenology form the basis of a common language used by psychiatrist to describe abnormal mental states. This conventional technique of clinical observation informed early studies on disturbances of thought form, speech and language observed in psychosis and schizophrenia. These findings resulted in language models that were used as tools in psychosis research that concerned itself with the links between formal thought disorder and language disturbances observed in schizophrenia. The end result was the development of clinical rating scales measuring severity of disturbances in speech, language and thought form. However, these linguistic measures do not fully capture the richness of human discourse and are time-consuming and subjective when measured against psychometric rating scales. Furthermore, these linguistic measures have never considered the influence of culture. With recent advances in computational sciences, we have seen a re-emergence of novel research using computing methods to analyze free speech for improving prediction and diagnosis of psychosis. Current studies on automated speech analysis examining for semantic incoherence are carried out based on natural language processing and acoustic analysis which in some studies have been combined with machine learning approaches for classification and prediction purposes. In this review, we first demonstrate a detailed description of the literature on diagnosis of schizophrenia in association with language and culture; then by focusing on computational methods, new computerized approaches are reviewed.